An Information System Landscape of Indonesia Tourism Destination - Azril Azahari; Sultan Sabiq Arrafi; D Damiasih; Aldi Wisnumurti (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Tourism and information technology are two things that are currently interrelated. The use of information technology in the tourism sector is very influential in its current development. One of the information technologies approaches used is the information system regarding tourist destinations in Indonesia. The use of the information system is used to make it easy for media users to access information about tourist destinations. All kinds of information conveyed from destinations, routes, attractions, facilities, and others are combined into one information system. In this paper, we present an information system landscape of indonesia tourism destination. We review information system usage for tourism destination. We show that the use of the information system for tourist location destinations can continue to be developed to get the trust of its users, starting from the facilities in the system, to the benefits of its use such as ease of search, ordering or reservation, and others. Finally, we present open problems for future research recommendations.